PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 125 PEKANBARU - Monalisa S; Eddy Noviana; Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This study aims to improve social studies learning outcomes by applying the Role Playing learning model to third grade students of SDN 125 Pekanbaru. This research is a class action research (PTK) with research subjects of class IIIB SDN 125 Pekanbaru. The results of the study indicate that social studies learning through the application of Role Playing learning models can improve social studies learning outcomes. This can be seen from: (1) teacher activity increases in each cycle. Teacher activity increased from the percentage of teacher activity in the first cycle by 75% (good category), in the second cycle it was 91.66% (very good category); (2) student learning activities increase in each cycle. Student learning activities increased from the percentage of student learning activities in the first cycle of 72.22% (sufficient category), in the second cycle was 94.44% (very good category); (3) Student learning outcomes increase from the average value before the action of 68.96, increasing in the first cycle of 9.91% with an average value of 75.8, and in the second cycle increased by 26.16% with an average value -rata 87.0. Based on the results of these studies, it can be concluded that using a Role Playing learning model can improve students' social studies learning outcomes.Keywords : Role Playing learning model, social studies learning outcomes, PTK